Model Rekrutmen Penyelenggara Pemilu yang Independen dan Berintegritas di Daerah Istimewa Yogyakarta - Suranto Suranto; Nasrullah Nasrullah; Tanto Lailam (The Constitutional Court of the Republic of Indonesia, 2020)
This study aims to find a model for the recruitment of election administrators with integrity and independence in the Special Region of Yogyakarta using qualitative research. The underlying problem is the large number of reports on election organizers who are not independent and have not integrity in various regions. To uncover these problems, the qualitative research with statutory, analytical, and case approaches is used. The results show that the recruitment model in the Law Number 12 Year 2008 still involves executive power (Governor or Regent/ Mayor), while the Law Number 15 Year 2011 and the Law Number 7 Year 2017 have better recruitment model and measurable process. The recruitment system contained in the Law Number 7 of 2017 is quite ideal, among the advantages of this system is that there is public involvement in the recruitment process, so the recruitment results are more accountable. Moreover, the current system is through the formation of a Selection Team consisting of academics, professionals, and community leaders who have integrity. However, some weaknesses still need to be fixed, namely: (1) the recruitment of the Selection Team must be conducted openly, (2) the integration of the CAT system in writing to ensure that candidates for election management have good theoretical and practical capabilities; (3) involvement of Provincial KPU and Provincial Bawaslu to select and determine candidates for election at Regency/ City level; (4) increasing public awareness that the Electoral Management Body (EMB) is an independent and professional institution so that political preferences can be eliminated.